Análisis comparativo de Casa de Geishas de Ana María Shua - Rangel Cuevas, Ana Gabriela (Universidad Michoacana de San Nicolás de Hidalgo, 2015)
This work is focused in the comparative analisis of Casa de gesishas of Ana María Shua. The first approximations we had made are to the concepts of microfiction and comparative literature. In the introduction there is also a short list of some of the works of Ana María Shua. The investigation has been organized in three blocks. The first one contains: a) the origins of the orientalism, proposed by Edward Said; b) the latinoamerican poetry and short narrative that has some oriental elements; c) the briefness as an element of “liason” between latinoamerican an oriental literature. The second chapter analyses the configuration of the house as a brothel, using the categories of the space and the iconic persons: the madame, the prostitutes and the clients. The last part has two sections, the intertexts and the metatextuality. Some of the intertexts that we reviewed are Snow White, Cinderella and the golem. In the part of the metatextuality, we have examined some of the microfictions which contain a reflection about the writing process.

Este trabajo está enfocado en el análisis comparativo de Casa de geishas de Ana María Shua. Las primeras aproximaciones que hemos hecho son de los conceptos de microrelato y literatura comparada. En la introducción hay también una pequeña lista de algunos de los trabajos de Ana María Shua. La investigación ha sido organizada en tres bloques. El primero contiene: a) el origen del orientalismo, propuesto por Edward Said; b) la poesía y la narrativa corta latinoamericana que tiene algunos elementos orientales; c) la brevedad como un elemento de “liason” entre la literatura latinoamericana y oriental. El segundo capítulo analiza la configuración de la casa como un burdel, usando las categorías de espacio y los personajes icónicos: la madama, las prostitutas y los clientes. La última parte contiene dos secciones, los intertextos y la metatextualidad. Algunos de los intertextos que revisamos son Blanca nieves, Cenicienta y el golem. En la parte de la metatextualidad, hemos examinado algunos de los microrrelatos que contienen una reflexión sobre el proceso de escritura.
Facultad de Letras. Maestría en Estudios del Discurso
Keywords: info:eu-repo/classification/cti/4; FL-M-2015-1277; Microrelato; Intertextualidad; Metatextualidad; Literatura latinoamericana; Orientalismo; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/136